Nanoparticles encapsulating phosphatidylinositol derivatives promote neuroprotection and functional improvement in preclinical models of ALS via a long-lasting activation of TRPML1 lysosomal channel - Valentina Tedeschi; Valeria Nele; Valeria Valsecchi; Serenella Anzilotti; Antonio Vinciguerra; Laura Zucaro; Maria Josè Sisalli; Chiara Cassiano; Nunzia De Iesu; Giuseppe Pignataro; Lorella Maria Teresa Canzoniero; Anna Pannaccione; et al. (Pharmacological Research)
Amyotrophic lateral sclerosis (ALS) is a progressive neurodegenerative disease currently incurable, in which motor neuron degeneration leads to voluntary skeletal muscle atrophy. Molecularly, ALS is characterized by protein aggregation, synaptic and organellar dysfunction, and Ca2+ dyshomeostasis. Of interest, autophagy dysfunction is emerging as one of the main putative targets of ALS therapy. A tune regulation of this cleansing process is affordable by a proper stimulation of TRPML1, one of the main lysosomal channels. However, TRPML1 activation by PI(3,5)P2 has low open probability to remain in an active conformation. To overcome this drawback we developed a lipid-based formulation of PI(3,5)P2 whose putative therapeutic potential has been tested in in vitro and in vivo ALS models.Pharmacodynamic properties of PI(3,5)P2 lipid-based formulations (F1 and F2) on TRPML1 activity have been characterized by means of patch-clamp electrophysiology and Fura-2AM video-imaging in motor neuronal cells. Once selected for the ability to stabilize TRPML1 activity, the most effective preparation F1 was studied in vivo to measure neuromuscular function and survival of SOD1G93A ALS mice, thereby establishing its therapeutic profile.F1, but not PI(3,5)P2 alone, stabilized the open state of the lysosomal channel TRPML1 and increased the persistence of intracellular calcium concentration ([Ca2+]i). Then, F1 was effective in delaying motor neuron loss, improving innervated endplants and muscle performance in SOD1G93A mice, extending overall lifespan by an average of 10 days. Of note F1 prevented gliosis and autophagy dysfunction in ALS mice by restoring PI(3,5)P2 level.Our novel self-assembling lipidic formulation for PI(3,5)P2 delivery exerts a neuroprotective effect in preclinical models of ALS mainly regulating dysfunctional autophagy through TRPML1 activity stabilization.